2003
DOI: 10.1007/s11916-003-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-related headache syndromes

Abstract: The relationship between sleep and sleep disorders and headache remains unclear. Clinical experience and numerous studies document some sort of relationship, but the exact nature remains understudied and complex. Changes in sleep duration and sleep quality appear to be capable of affecting headaches of different types. Obstructive sleep apnea can cause or exacerbate headaches in a susceptible person. Obstructive sleep apnea also may cause a specific headache when awakening, which is different from migraine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
(39 reference statements)
0
7
0
1
Order By: Relevance
“…Several authors have suggested the hypothalamus as the location from which this dysfunction might originate because of its connection to the brainstem and its important role in both pain and sleep regulation [6, 8, 58, 59]. Moreover, studies using MRI have reported activation of the brainstem [60, 61] and the hypothalamus [62] during headache attacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested the hypothalamus as the location from which this dysfunction might originate because of its connection to the brainstem and its important role in both pain and sleep regulation [6, 8, 58, 59]. Moreover, studies using MRI have reported activation of the brainstem [60, 61] and the hypothalamus [62] during headache attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep-related symptoms are associated with painful conditions [4], partly because pain may interfere with sleep and vice versa [5]. This dual cause and effect relationship has been known for many years through clinical experience with headache patients [6, 7], and the scientific literature about the comorbidity of headache and sleep disturbances are growing [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Patients with migraine tend to have several problems with sleep quality and continuity [7,8]. Studies have also shown that patients with narcolepsy have a significantly higher prevalence of migraine [9] as compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…However, these factors may also play a role in headache pathogenesis (21, 22). Additionally, OSAS is believed to be a trigger for attacks in migraine patients (23).…”
mentioning
confidence: 99%